ASSESSING THE RELATIONSHIP OF CLIMATE VARIABILITY AND CROP PRODUCTION IN BAUCHI TOWN AND ENVIRON - YAHAYA I; BELLO M. B; RUKAYYA M. M; YUGUDA A. I (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
The study examines the relationship between climate variability and crop production in Bauchi town and its environs. Climatic elements such as rainfall and temperature were obtained from the Nigerian Meteorological Agency (NIMET) in Bauchi for three decades (1981-2010) and crop yield of some selected crops such as maize, millet, rice, sorghum, groundnut and cowpea were sourced from the Bauchi State Agricultural Development Programme (BSADP) for 30years (1981-2010). These data were analysed using correlation and simple linear regression analysis. The results obtained reveals that rice and cowpea show significant relationship with rainfall at 0.05 level of significant while maize, millet, sorghum and groundnut shows no significant relationship. Temperature and Rainfall explain 10% crop yield of the selected crops but will explain better other crops not included in the study. This implies that other environmental factors such as soil fertility, agricultural inputs may explain better the variation between climatic variable and the selected crop yield. As a result, it was recommended that crop yield should be regressed on other environmental factors such as soil fertility and agricultural inputs. More investment should be made on rain fed agriculture using agricultural extension service.